Analyzing Student Perceptions on Translanguaging: A Case Study of a Puerto Rican University Classroom - Adrian J. Rivera; Catherine M. Mazak (Asociación Colombiana de Profesores de Ingles, 2017)
Translanguaging in the classroom is gaining traction as a viable pedagogical choice. Often overlooked, though, are the students' attitudes in response to strategic classroom translanguaging. This study seeks to determine whether students' language attitudes influence their perceptions of an instructor's translingual pedagogy. The study took place in an undergraduate psychology classroom at the University of Puerto Rico, Mayagüez, and involved a case-study approach and analysis of survey results. The results show this particular group of students has a neutral to positive outlook on classroom translanguaging. The high number of neutral responses may mean students are indifferent to translingual pedagogy or that these students are conditioned to work within a context where code switching and translanguaging happen frequently.